Water Absorption of Fluids/Oils. - Jamison,Robert G (1978)
The object of the investigation was to determine the effects of water absorption on the inhibitor systems and basestocks of various hydraulic fluids and engine oils. From this experimentation, a need was generated to develop a more accurate method for analyzing water in these fluids and oils. The results subsequently obtained verified the fact that absorbed water affects the stability of the inhibited fluid and oil systems. (Author)